Cytoplasmic epigenetics: inheritance by cytoplasmic continuity - Silar, Philippe; Malagnac, Fabienne (Henry Stewart Talks, 2007)
Description in microbes of heritable phenomena not based on nucleic acids, fundamental importance of these phenomena in fully understanding inheritance, transmittance through cellular continuity, molecular mechanisms, template assisted folding of macromolecular structures, self-perpetuating metabolic circuitry
Reviewed at 2016/02/12